2011
DOI: 10.1007/s10725-011-9615-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biomass and steviol glycosides in Stevia rebaudiana treated with phosphate-solubilizing bacteria and rock phosphate

Abstract: Biofertilizers offer alternative means to promoting cultivation of medicinal plants less dependent on chemical fertilizers. Present study was aimed at evaluating the potential of phosphate-solubilizing bacteria (PSB) Burkholderia gladioli MTCC 10216, B. gladioli MTCC 10217, Enterobacter aerogenes MTCC 10208 and Serratia marcescens MTCC 10238 for utilizing Mussoorie rock phosphate (MRP) to enhance plant growth, and stevioside (ST) and rebaudioside-A (R-A) contents of Stevia rebaudiana. The solubilization of MRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
(35 reference statements)
1
23
1
2
Order By: Relevance
“…The lowest values of nitrogen, phosphorus and potassium contents (1.50, 0.19 and 1.52%,) were found with control (80 kg N fed -1 ), while, compost + 50% of the control treatment scored the highest values (1.63, 0.28 and 2.11%), respectively. The aforementioned findings correlated with those recorded by Gupta, (2010); Gupta, et al (2011);Khaled & Fawy(2011) and Kumar, et al (2012 and2013) who reached the same results. In this subject, they revealed that increase in K% of stevia leaf by compost application might be due to enhancement in K availability by shifting the equilibrium among the forms of K from relatively exchangeable K to soluble K forms in the soil.…”
Section: Ii-plant Nutrient Statussupporting
confidence: 90%
See 2 more Smart Citations
“…The lowest values of nitrogen, phosphorus and potassium contents (1.50, 0.19 and 1.52%,) were found with control (80 kg N fed -1 ), while, compost + 50% of the control treatment scored the highest values (1.63, 0.28 and 2.11%), respectively. The aforementioned findings correlated with those recorded by Gupta, (2010); Gupta, et al (2011);Khaled & Fawy(2011) and Kumar, et al (2012 and2013) who reached the same results. In this subject, they revealed that increase in K% of stevia leaf by compost application might be due to enhancement in K availability by shifting the equilibrium among the forms of K from relatively exchangeable K to soluble K forms in the soil.…”
Section: Ii-plant Nutrient Statussupporting
confidence: 90%
“…The recorded results in this work Rodriguez & Fraga (1999) ;Gupta, (2010) ;Gupta, et al (2011) and Kumar, et al (2012Kumar, et al ( , 2013Kumar, et al ( and 2014 who revealed that application of biofertilizer improved the root activity and enhanced the photosynthesis, finally the biomass of stevia was increased. They added that this increase might be due to bacterial inoculation may be attributed to their effect on nitrogen fixation.…”
Section: Iii-yields Of Stevia Rebaudianamentioning
confidence: 54%
See 1 more Smart Citation
“…and B. lentus signifi cantly increased proline, total carbohydrate, chlorophyll, and nutrient uptake under water stress. Gupta et al ( 2011 ) evaluated the prospective uses of phosphate-solubilizing bacterial strains such as Burkholderia gladioli , B. gladioli , Enterobacter aerogenes , and Serratia marcescens to utilize Mussoorie rock phosphate and to improve the growth of Stevia rebaudiana and secondary metabolites (stevioside and rebaudioside A). They concluded that a signifi cant increase in plant growth and metabolite production (stevioside and rebaudioside A) was recorded in the plants treated with combination of bacterial strains grown in Mussoorie rock phosphate amended soil compared to unamended soil.…”
Section: Effect Of Pgprs and Am Fungi On The Growth And Development Omentioning
confidence: 99%
“…Among these, organic amendments, including animal manure, plant residues and green manure (Alloush, 2003;Toor, 2009;Aria et al, 2010;Adesanwo et al, 2012), composts (Nishanth and Biswas, 2008;Wickramatilake et al, 2010;Saleem et al, 2013), and bacterial inoculation (Panhwar et al, 2011;Gupta et al, 2011) are considered beneficial for improving the P efficiency. In addition, the combined application of water-soluble P fertilizers with RP is another option to increase the efficiency of RP P. Mashori et al (2013) used maize as a test crop in a pot experiment to examine the relative performance of RP, single superphosphate (SSP) and RP+SSP with and without farm yard manure (FYM).…”
Section: K Abbasi Et Al: Efficiency Of Rock Phosphate With Psbmentioning
confidence: 99%